O gênero discursivo parábola na prática de sala de aula : uma proposta de didatização - Estevão, Adriana Gisele (2016)
For the purpose of effecting a Portuguese Language teaching more contextualized, this participant qualitative-interpretive research study has the general objective to didactization of the discourse genre parable. For a long time, the parable remained like a genre restricted to the religious sphere, with specific characteristics that have been developed and transformed the parable narratives in a genre of literary sphere. Today, the parable is present in various discursive practices and thus, through the study of its characteristics as discourse genre - theme content, compositional construction and style - we try to establish the regularities and instabilities of the genre, anchoring us study scholars as Sant'Anna (1998, 2010) and the analysis of several concrete statements of the genre. As a theoretical framework for the study of language, the research is based on the dialogical conception proposed by Bakhtin (2003), which assumes the interactional character as the language of reality, considering the discourse as a social practice which is realized through the discourse genres. For the process of didactization genre parable, this work appropriates the didactic model of Didactic Sequences proposed by Dolz, Noverraz and Schnewly (2010). After the development of educational routing proposal, which develop reading, writing and linguistic analysis activities, was carried out the implementation in a ninth grade class of elementary school and being a research in Applied Linguistics, such as data collection instruments appealed himself to recordings of classes, field diaries and questionnaires during the implementation for further analysis. In this sense, the study on the screen, establishing itself from the analysis of the collected data, noting that the interactive relationships triggered school environment through didactic proposal starting from a unique genre in the classroom as the parable leads to a teaching of fruitful and contextualized mother tongue, as can be seen from the results. In terms of theme, style and compositional construction perceives at the end of work, even before some imponderables arising during the implementation of the research, the results were positive.